2018
DOI: 10.21521/mw.6054
|View full text |Cite
|
Sign up to set email alerts
|

Circulating concentrations of insulin like growth factor-1 in female dogs with spontane-ous mammary tumours

Abstract: SummaryThe aim of this study was the investigation of the circulating concentration of IGF-1 in female dogs with spontaneous mammary tumours. The study was performed on 34 female dogs undergoing surgery due to spontaneously occurring mammary gland tumours (24 malignant and 10 benign) and 10 clinically healthy female dogs. The serum concentrations of IGF-1 were determined by specific ELISA Kit assay. The mean concentrations of IGF-1 were significantly higher (P < 0.05) both in dogs with malignant (173.35 ± 120.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Recently, circulating IGFs have also been studied in veterinary medicine. Several studies have shown that the serum IGF-I concentration in dogs with mammary gland tumors is higher than that in healthy dogs [ 9 21 ]. These results are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, circulating IGFs have also been studied in veterinary medicine. Several studies have shown that the serum IGF-I concentration in dogs with mammary gland tumors is higher than that in healthy dogs [ 9 21 ]. These results are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, excessive IGF-I and IGF-II expression causes the cells to over-proliferate and interfere with apoptosis, inducing tumors [ 3 ]. In veterinary medicine, studies on IGF-I have also been reported in relation to tumors, but there is a significant difference in the methodology for measuring the concentration, which may be unreliable [ 4 5 6 7 8 9 ]. In addition, in the case of IGF-II, there are only a few reports on veterinary research [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation